Study on Profitability of Combining Wood and CFRP into Composite Based on Mechanical Performance of Bent Beams - Bartosz Kawecki; Andrzej Sumorek (Applied Sciences, 2022)
The paper attempts to estimate the profitability of combining wood and CFRP into a composite (BSH-CFRP), intended to be used in load-bearing beams, including mechanical performance and prices of constituent materials. Prices of glue laminated timber (BSH) and CFRP tapes over the years were provided by ABIES Poland Ltd. and S&P Poland Ltd. companies. Referring to the uncertainty of wood prices on the market, two levels of BSH prices were adopted. A prediction of the beams’ mechanical behaviour was made based on the analytical model prepared by the author. The calculated members varied in width, height and length and included twelve types of CFRP tapes (different thickness, width and modulus of elasticity) glued between wooden lamellas. The total cost of each BSH-CFRP beam was compared to the total cost of the corresponding BSH beam in GL24h class, which led to calculating a cost multiplier. Consecutively, the multiplier was referred to the standard class improvement of BSH according to the bending stiffness and load-bearing capacity. A cloud of points got from many analyses resulted in obtaining exponential approximating functions. The averaged results led to general conclusions that at the assumed price level, improving the BSH standard class by using CFRP tapes was associated with a 1.86 BSH cost in the case of expensive wood or 2.81 in the case of cheap wood. Improving class by two was connected with the 3.55 BSH cost for expensive wood, and 6.79 for cheap wood. At present, the profits from composing wood with CFRP appear to be not very high in terms of their price. However, they can radically increase, especially when wood cutting limits are imposed on manufacturing companies, which significantly reduce the available timber for construction use.